Conscientious Objection and the Treaty with the Holy See and other registered Churches (Stato, Chiese e pluralismo confessionale, 2015)
Paper for the International Conference «The Importance of Application of the Freedom of Conscience in a Democratic Society», 21 May 2015, organised by Trnava University, Faculty of Law, Slovakia, to be published in the Conference Proceedings